PERCEIVED ENTITLEMENT AND OBLIGATION BETWEEN TIKTOK CREATORS AND AUDIENCES - Watson, TX (AoIR Selected Papers of Internet Research, 2023)
In 2020 TikTok saw an influx of new users, looking for a sense of relief in the face of overwhelming loneliness, and found some palliative comfort in the sense of intimacy entailed in engaging with the works of microcelebrities. At the same time many new users became creators on TikTok, saw incredible growth, and quickly found themselves navigating a larger scale of demands on their attention and on their affects than they’d ever experienced, or, usually, expected. The purpose of this paper is to examine and describe the specific demands on the affective labor and attention of content creators on TikTok, the ways in which those demands tend to exceed what the creators themselves are comfortable with or capable of sustaining, and the challenges and limitations that prevent creators from setting, communicating, or maintaining boundaries around their labor, relationships, or personal and professional lives. I investigated these questions by participant observation and a series of interviews and explore answers in an ethnographic and autoethnographic framework. Audience members treat the emotional experience of creators as an open resource in two ways: 1) externalization, placing difficult emotional experiences in the creator’s hands with the expectation that the creator will do something about it, and so the audience member doesn’t have to; and 2) extraction, soliciting the public performance of an emotional reaction to material of the audience member’s choice. The dehumanizing experience of being treated as vending machines for intimacy is an ongoing psychological harm that, to some extent, all microcelebrities endure.